Biochar application for sustainable soil erosion control: a review of current research and future perspectives - Sharma, Prabhakar (Frontiers in Environmental Science, 2024)
Soil erosion is a pressing environmental issue with significant agricultural productivity and ecosystem stability implications. In recent years, biochar, a carbon-rich product of biomass pyrolysis, has emerged as a promising soil amendment tool for erosion control due to its ability to improve soil quality and stability. This review paper aims to comprehensively analyze the effectiveness of biochar role in mitigation of soil erosion and sustainable land management practices. By examining a wide range of research studies, this paper elucidates the impact of biochar on key soil erosion parameters as it directly affects the soil structure, water-holding capacity, and nutrient retention. The paper discusses how biochar interacts with soil particles and aggregates to enhance their stability and resistance to erosive forces. It also assesses the influence of biochar properties, such as feedstock type, pyrolysis temperature, and application rate, on its erosion control efficacy. Furthermore, this review explores the role of biochar in promoting plant growth and root development, thereby reinforcing the vegetation cover and further reducing erosion susceptibility. Finally, an outline of potential challenges and opportunities for the widespread adoption of biochar-based erosion control strategies in different agricultural and environmental contexts is presented. Overall, this review provides valuable insights into the multifaceted role of biochar in sustainable soil management and offers recommendations for future research directions on direct and indirect application on soil erosion control.